Encouraging Self-Empowerment and Innovationfor Students' Entrepreneurial Potentialin Maahad Tahfiz Darul Fuqaha, Malaysia - Suratman, Andriyastuti; Nursyamsiah, Siti; Muzakir, Mellisa Fitri Andriyani; Mansyur, Saddam Murtadho; Rifanandi, Rifai Iqbal; Rasipu, Muhammad Nur Alim; Azmi, Afra Nabilah Taqiyyah; Wulandari, Rifana (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2026)
This activity introduces entrepreneurship to children and adolescents at Maahad Tahfiz Anak Yatim Darul Fuqaha, Kajang, Selangor, Malaysia. With an interactive one-day training, participants are expected to develop a creative and optimistic entrepreneurial spirit. The material is delivered through simple storytelling, accompanied by icebreaking and questions and answers, thus triggering the participants' enthusiasm. As a result, the training succeeded in increasing the understanding and motivation of participants regarding the importance of entrepreneurship for future independence. However, it was found that children need continuous assistance to empower themselves optimally.The main challenge is to involve the role of adult companions, such as teachers or caretakers of the orphanage, to guide children to develop creativity and self-motivation. This training instills self-empowerment, a creative mindset, and a spirit of independent living. Through this training, children realize that the limitations of living in an orphanage are not a barrier to development. The focus is changing the mindset from job seekers to business opportunity creators. The implications of this activity include improving the quality of life of participants and the potential for scientific publications to share the results of the training with the broader community.